2017
DOI: 10.1038/srep41653
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Polymorphisms Predisposing to Bronchiolitis

Abstract: Bronchiolitis is a major cause of hospitalization among infants. Severe bronchiolitis is associated with later asthma, suggesting a common genetic predisposition. Genetic background of bronchiolitis is not well characterized. To identify polymorphisms associated with bronchiolitis, we conducted a genome-wide association study (GWAS) in which 5,300,000 single nucleotide polymorphisms (SNPs) were tested for association in a Finnish–Swedish population of 217 children hospitalized for bronchiolitis and 778 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…2 By the age of 2 years, nearly all children have been infected with RSV at least once, yet only 1-3% develop a severe disease requiring hospitalization, 2,3 suggesting a genetic predisposition to develop a severe disease. [4][5][6][7][8][9] In agreement with this possibility, a twin cohort study revealed a higher concordance in the hospitalization rates of identical twins when compared to fraternal twins, estimating that approximately 20% of the propensity to develop severe bronchiolitis upon RSV infection was attributable to genetic differences. 10 The potential relevance of genetic background to the degree of severity of bronchiolitis is further reinforced by the differences in the rate of RSV hospitalization observed in populations from different racial and ethnic backgrounds living in the same geographic region or country.…”
Section: Introductionmentioning
confidence: 74%
“…2 By the age of 2 years, nearly all children have been infected with RSV at least once, yet only 1-3% develop a severe disease requiring hospitalization, 2,3 suggesting a genetic predisposition to develop a severe disease. [4][5][6][7][8][9] In agreement with this possibility, a twin cohort study revealed a higher concordance in the hospitalization rates of identical twins when compared to fraternal twins, estimating that approximately 20% of the propensity to develop severe bronchiolitis upon RSV infection was attributable to genetic differences. 10 The potential relevance of genetic background to the degree of severity of bronchiolitis is further reinforced by the differences in the rate of RSV hospitalization observed in populations from different racial and ethnic backgrounds living in the same geographic region or country.…”
Section: Introductionmentioning
confidence: 74%
“…23 At present, genome-wide association studies (GWAS), including replication of identified loci, are the preferred method for gene discovery, but only one, relatively small, GWAS of bronchiolitis have been performed without genome-wide significant findings. 24 A number of susceptibility genes have been suggested from candidate gene studies.…”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%
“…Genetic discoveries in GWAS require a very large number of participants, and large well-powered GWAS of respiratory viral infections per se have not yet been performed. One smaller GWAS of bronchiolitis was performed without genome-wide significant findings [34]. Candidate gene studies, most focusing on RSV bronchiolitis, have suggested several susceptibility genes related to immune regulation and surfactant proteins [35].…”
Section: Genetics and Epigenetics Of Asthma And Virus Susceptibilitymentioning
confidence: 99%